Fundamentals and aeroacoustics with applications in aeropropulsion systems - Sun, Xiaofeng; Wang, Xiaoyu (Elsevier and Shanghai Jiao Tong University Press aerospace series., 2021)
Fundamentals of Aeroacoustics with Applications to Aeropropulsion Systems from the Shanghai Jiao Tong University Press Aerospace series, is the go-to reference on the topic, providing a modern take on the fundamental theory and applications relating to prediction and control of all major noise sources in aeropropulsion systems. This important reference compiles the latest knowledge and research advances, considering both the physics of aerodynamic noise generation in aero-engines and related numerical prediction techniques. Additionally, it introduces new vortex sound interaction models, a transfer element method, and a combustion instability model developed by the authors. Focusing on propulsion systems from inlet to exit, including combustion noise, this new resource will aid graduate students, researchers, and R & D engineers in solving the aircraft noise problems that currently challenge the industry. Updates the knowledge-base on the sound source generated by aeropropulsion systems, from inlet to exit, including combustion noise. Covers new aerodynamic noise control technology aimed at the low-noise design of next generation aero-engines, including topics such as aerodynamic noise and aero-engine noise control. Includes new, cutting-edge models and methods developed by an author team led by the editor-in-chief of the Chinese Journal of Aeronautics and Astronautics. Considers both the physics of aerodynamic noise generation in aero-engines and related numerical prediction techniques.